Nigerian Local Government’s, Inter-Governmental Performance and Relations : The Fourth Republic (1999 to Date) Selected. - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Forum of Researchers and Lecturers, 2025)
Over the years, there have been issues with the relationship between Nigeria's three levels of government. Numerous committees and commissions have been established, and suggestions have been made, but until the levels of government continue to clash over finances today. Being the third level of government, the local government has been hardest damaged, which has made it impossible for it to successfully perform its mandated duties. Because of this, this study looked at Nigerian local government performance and intergovernmental relations. The study used a survey design, with a focus on descriptive research. Focus groups and questionnaires were used to gather data. The Central Bank of Nigeria and government documents provided the secondary data. Among other things, the results showed that intergovernmental relations have somewhat eased tensions between Nigeria's three levels of government. Additionally, the 1999 constitution's flaws have hindered fiscal relationship among Nigeria's three levels of government. Among other things, the research suggested that efforts be made to guarantee that all levels of government follow the constitutional rules on budgetary relations, accountability, and openness.